Pregnancy and Pandemic: Impact of Covid-19 on Maternity Care and Psychosocial Well-Being of Pregnant Women in India - Thota, Sowmya; Reddy, Radha; Kaur, Inderjeet; Loughnan, Siobhan; Gautam, Rupesh; Reddy, Gopireddy Murali Mohan (Women, Midwives and Midwifery, 2025)
Background: The COVID-19 pandemic significantly disrupted maternity care and affected the psychosocial well-being of pregnant women in India. Purpose: This study examines the impact of COVID-19 on access to maternity care, psychosocial health, and information satisfaction among pregnant women in South India. Methods: A cross-sectional study was conducted in tertiary hospitals in South India between September 2020 and January 2021 as part of the global COCOON study. A convenience sample of 321 pregnant women receiving antenatal care participated in an online survey available in English and Telugu. Psychosocial well-being was assessed using validated scales: State-Trait Anxiety Inventory (STAI), Edinburgh Postnatal Depression Scale (EPDS), Perceived Stress Scale (PSS-4), and De Jong Gierveld Loneliness Scale (DJGLS). Results: Despite the pandemic, 87.2% of women continued attending antenatal check-ups. However, 44% reported moderate-to-severe anxiety, 52% experienced depressive symptoms, 91% had high stress levels, and 82% felt lonely. Additionally, domestic violence increased by 10%, while 58% of participants reported strengthened family connections. Healthcare providers emerged as the most trusted information source (79%). Conclusion: "Despite continued access to maternity care, the pandemic significantly impacted the psychosocial well-being of pregnant women. Integrating routine mental health screening and support into antenatal care is crucial to improving maternal well-being and ensuring resilient maternity services during public health emergencies."